Macro Mineral Status in Soil, Plant and Dairy Cattle in Andaman Group of Islands - Hegde, M. Sujata (Indian Journal of Animal Nutrition, 2018)
Present work was carried out in Prothrapur, Ferrargunj, Little Andaman, Diglipur, Rangat and Mayabunder blocks of the Andaman group of Island with the objective to estimate macro minerals status in soil, composite plant samples and dairy cattle. Samples of soil, composite plant and cattle blood serum each totalling 102 were taken randomly from all the six blocks. The samples were analysed for macro minerals (Ca, P, Mg, Na and K). The soil was deficient in Ca, P and Mg. The overall mean concentration of Mg (135.81Â±17.4 ppm) and P (9.42Â±0.59 ppm) in soil differed significantly (P